2005
DOI: 10.1136/jme.2004.010595
|View full text |Cite
|
Sign up to set email alerts
|

Project Examining Effectiveness in Clinical Ethics (PEECE): phase 1—descriptive analysis of nine clinical ethics services

Abstract: Objective:The field of clinical ethics is relatively new and expanding. Best practices in clinical ethics against which one can benchmark performance have not been clearly articulated. The first step in developing benchmarks of clinical ethics services is to identify and understand current practices.Design and setting:Using a retrospective case study approach, the structure, activities, and resources of nine clinical ethics services in a large metropolitan centre are described, compared, and contrasted.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…This finding may be important in guiding the development of ethics support services in Europe. It may also be relevant elsewhere: intentionally developing less formal resources has also been proposed as a way to increase the effectiveness of formal ethics support services in Canada [19]. It must be noted that integrating the diversity of informal support would lead us in a direction opposite to that advocated by most health services recommendations, that is, to formalize, codify, and explicitly reduce variation.…”
Section: Discussionmentioning
confidence: 97%
“…This finding may be important in guiding the development of ethics support services in Europe. It may also be relevant elsewhere: intentionally developing less formal resources has also been proposed as a way to increase the effectiveness of formal ethics support services in Canada [19]. It must be noted that integrating the diversity of informal support would lead us in a direction opposite to that advocated by most health services recommendations, that is, to formalize, codify, and explicitly reduce variation.…”
Section: Discussionmentioning
confidence: 97%
“…Most studies of ethics support services have sought to establish aspects such as: the prevalence of support services, their type, structure, composition, main functions, activities and processes (see for example McGee et al, 2001;Slowther et al, , 2004Slowther, McClimans, and Price, 2012;Godkin et al, 2005;Milmore, 2006;Fox, Myers, and Pearlman, 2007;Frewer and Fahr, 2007;Swetz et al, 2007;Pedersen, Akre, and Førde, 2009;Romano et al, 2009;Whitehead et al, 2009;Kesselheim, Johnson, and Joffe, 2010;Gaudine et al, 2010;Nelson et al, 2010b;Tapper et al, 2010;Moeller et al, 2012). What these studies mostly show is the diversity of CES services.…”
Section: Evaluation Of Ces Servicesmentioning
confidence: 99%
“…There is considerable variation in the model of consultation used by hospitals. For example, Godkin et al's (2005) study of ethics consultation in nine Toronto hospitals found that consultation was usually done by independent consultants, while Racine (2007) notes that 75% of Quebec ethics committees do consultations. In a US national survey, 68% of consultations were done by a small team, 23% by a full ethics committee and 9% by an individual consultant (Fox et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Although some studies have focused on the ethics consultation function in hospitals, it is clear that some hospitals do not use committees to actually do consultations. For example, Godkin et al (2005) examined nine clinical ethics services in a Canadian city and all but one used an independent consultant for ethics consultations, although six of the nine sites had ethics committees. In addition, a high degree of variability in clinical ethics services was one of the notable themes of the study.…”
mentioning
confidence: 99%